2012
DOI: 10.1111/j.1749-6632.2012.06737.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, metabolic dysregulation, and cancer: a growing concern and an inflammatory (and microenvironmental) issue

Abstract: Obesity is an established risk and progression factor for many cancers. In the United States more than one-third of adults, and nearly one in five children, are currently obese. Thus, a better understanding of the mechanistic links between obesity and cancer is urgently needed to identify intervention targets and strategies to offset the procancer effects of obesity. This review synthesizes the evidence on key biological mechanisms underlying the obesity–cancer association, with particular emphasis on obesity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 55 publications
1
106
0
2
Order By: Relevance
“…Reiterating geneenvironment interaction, numerous studies have shown a prevalence of metabolic dysregulation among breast cancer cases. Elevated fasting blood glucose (13), elevated leptin (14), and obesity (15) have been associated with increased risk of breast cancer, particularly among postmenopausal women. Adipose tissue supports carcinogenesis by secreting growth factors and cytokines (16,17) that can possibly be modulated as future preventive and therapeutic measures.…”
Section: Discussionmentioning
confidence: 99%
“…Reiterating geneenvironment interaction, numerous studies have shown a prevalence of metabolic dysregulation among breast cancer cases. Elevated fasting blood glucose (13), elevated leptin (14), and obesity (15) have been associated with increased risk of breast cancer, particularly among postmenopausal women. Adipose tissue supports carcinogenesis by secreting growth factors and cytokines (16,17) that can possibly be modulated as future preventive and therapeutic measures.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies that followed supported the association of elevated body mass index (BMI), metabolic disordersincluding hyperglycemia, hyperinsulinemia, dyslipidemia, type 2 diabetes, and hypertension and visceral adiposity with the risk of CRC and colon carcinogenesis [9]. Adipose tissue, which is viewed like glandular tissue, performing endocrine, paracrine and autocrine functions, has been found key in the process of neoplastic transformation, especially in inhibiting the anti-lipolytic effect of insulin [10][11][12][13][14][15]. Two specific hormonal systems, adipokines and the insulin/insulin-like growth factor (IGF) axis, are the most studied metabolic biomarkers of CRC [16,17].…”
Section: Metabolic Biomarkersmentioning
confidence: 99%
“…Various medical treatments are available to regulate glucose dysregulation, correct hormonal changes and vascular conditions in DM patients; however, these medical treatments cannot always cure the metabolic disorder completely, and physicians also cannot predict the progression of the complications with uncontrolled patient's life styles [20][21][22][23][24] . Particularly T2DM is significantly related to the incidence of obesity and its associated disorders [25][26][27] . Obesity is defined as a surplus of body fat accumulation, with the excess of adipose tissue really being a well-established metabolic risk factor for the development of obesity-related comorbidities such as insulin resistance, T2DM, cardiovascular diseases, and some common cancers [2,[28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is defined as a surplus of body fat accumulation, with the excess of adipose tissue really being a well-established metabolic risk factor for the development of obesity-related comorbidities such as insulin resistance, T2DM, cardiovascular diseases, and some common cancers [2,[28][29][30][31][32] . The mechanisms linking excess adiposity and cancer are unclear, but the obesity-related low-grade chronic inflammation is widely accepted as a critical factor in the pathogenesis of various diseases such as T2DM, cardiovascular disorders, dementia, cancers, dietary control failure [26,28,[33][34][35][36][37][38][39][40][41][42] . Currently, particular attention has been placed on the pro-inflammatory microenvironment in the body associated with obesity, specifically underlining the involvement of obesity-associated hormones/growth factors in the cross-talk between macrophages, lymphocytes, adipocytes, and epithelial cells involved in the development of T2DM [28,43] .…”
Section: Introductionmentioning
confidence: 99%